Environment Carrying Capacity Analysis of the Cibinong Situ Plaza as a Public Green Open Space - Feliza Alvi Monica; Tatan Sukwika; PS. Dyah Prinajati (The Graduate School of Sahid University, 2023)
Cibinong Situ Plaza is a Public Green Open Space (PGOS) with a unique tourism potential: the transition from water and land ecosystems (ecotone). PGOS Cibinong Situ Plaza is the leading free recreation destination that is complete for Cibinong City residents and its surroundings. The level of visits is very crowded and dense, which is a new problem for environmental sustainability there. Therefore, to support recreational activities, it is necessary to carry out an analysis of the carrying capacity of the environment to determine the maximum threshold for the number of tourists who are in the tourist area at the same time. The analytical method uses the physical carrying capacity (PCC), real carrying capacity (RCC) and effective carrying capacity (ECC) approaches. The calculation results obtained PCC values of 684 people per day, RCC 22 people per day, and ECC 20 people per day. The actual number of tourists throughout 2019-2020 is known to be 25 people per day. The conclusion shows that the number of tourists is still below the capacity of the Cibinong Situ Plaza PGOS. Follow-up studies need to explore the preferences and level of interest of tourists regarding tourist facilities to determine the satisfaction of visiting tourists.